Frequency of Scholarship on Counselling Males in the Canadian Journal of Counselling and Psychotherapy - Hoover, Stuart M.; Bedi, Robinder P.; Beall, Lauren K. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article examines the frequency with which studies on boys/men are represented in Canadian counselling scholarship, as embodied in the Canadian Journal of Counselling and Psychotherapy (CJCP). To address this question, a quantitative content analysis was conducted of articles published in CJCP from 2000 (Volume 34, Number 1) to 2011 (Volume 45, Number 2). Results indicate that authors and researchers who publish in CJCP overwhelmingly study females rather than males, at a ratio of about 12 to 1. This raises questions regarding the absence of boys/men in Canadian counselling scholarship and provides a defensible rationale for the further study of males and counselling.